FAMILY HEALTH CARE COSTS OF LIFESTYLE DISEASES - V. VIJAYA LAKSHMI, N. PAVANI, D. RATNA KUMARI and (The Journal of Research, PJTSAU, 2017)
Health care has emerged as one of the most progressive and target sector in India, with a GDP spend of 8 per cent in 2012 up from 5.5 per cent in 2009. Health care in India is at an inflection point now and is poised to grow up to US 280 billion by 2020 which is a growth of over ten times since 2005 (Source: Indian Hospital Services Market Outlook).